Health promotion in adults with Down's syndrome: Experiences of caregivers. (September 2021) - Borthwick, Claire; Inchley, Joanna; Jones, Jill
Individuals with Down's syndrome rely on caregivers to support lifestyle behaviour change. It is therefore important to understand how caregivers put health recommendations into practice. Through conducting semi-structured interviews, the present study sought to understand the facilitators and barriers that caregivers faced when implementing health promotion advice. Five interviews were conducted with paid support staff and four with family carers of individuals attending a specialist multidisciplinary Down's syndrome health promotion screening clinic. Three main themes emerged in their accounts, including active promotion of weight management by caregivers, benefits of working practices such as record keeping and communication channels and the importance of having access to social care services and recreational activities. These findings have important implications for professionals working in specialised healthcare settings who may be able to tailor communication and services to better meet the needs of individuals with Down's syndrome and their caregivers.